Overcoming Immune Evasion in Staphylococcus aureus : Strategies for Rational Vaccine Design. - Shinwari, Khyber; Vieira, Brenda; Ciaparin, Isabelle; Hakansson, Anders P ; 0000-0002-2834-6009; Darrieux, Michelle; Converso, Thiago Rojas (ACS Infectious Diseases, 2025)
Staphylococcus aureus remains one of the most elusive targets in bacterial vaccinology, primarily due to its complex immune evasion strategies and the phenomenon of immune imprinting. Despite decades of research and numerous clinical trials, no vaccine has demonstrated protective efficacy in humans. This review examines the underlying reasons for these failures and proposes a rational, integrative framework for next-generation vaccine development. Recent advances in reverse vaccinology, omics-driven antigen discovery, immunoinformatics, and artificial intelligence are highlighted as tools to identify conserved, immunogenic, and subdominant antigens. The review also discusses approaches for neutralizing virulence factors, disrupting biofilm-associated mechanisms, and circumventing dysfunctional immune memory. Particular emphasis is placed on the design of multivalent vaccine formulations capable of addressing the antigenic redundancy and immune modulation employed by S. aureus. By aligning systems biology with precision vaccinology, this review outlines a translational strategy to overcome the long-standing obstacles in the development of a safe and effective S. aureus vaccine.
Keywords: Immune Evasion; Humans; Staphylococcus aureus/immunology; Staphylococcal Vaccines/immunology; Staphylococcal Infections/prevention & control; Vaccine Development; Virulence Factors/immunology; Animals; Antigens, Bacterial/immunology; Vaccinology